Loss of Pleckstrin homology like domain, family A, member 1 promotes type Ⅱ alveolar epithelial cell apoptosis in chronic obstructive pulmonary disease emphysematous phenotype via interaction with tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein epsilon. (October 2022) - Bai, Shuang; Ye, Rui; Wang, Cuihong; Sun, Pengbo; Wang, Di; Yue, Yong; Wang, Huiying; Wu, Si; Yu, Miao; Xi, Shuhua; Zhao, Li
Abstract: Emphysematous phenotype is the most important phenotypic component of chronic obstructive pulmonary disease and is associated with substantial morbidity and mortality. The current pharmaceutical treatments and therapeutic procedures do not reduce pulmonary damage in patients with emphysematous phenotype. Therefore, it is important to identify effector molecules that can be used as interfering targets in such patients. Apoptosis of type II alveolar epithelial cells plays a key role in the phenotypic formation. This study aimed to further explore the molecular mechanisms involved in this process. The number of type II alveolar epithelial cells was significantly reduced due to increased apoptosis in patients with emphysematous phenotype compared to those with non-emphysematous phenotype. Pleckstrin homology like domain, family A, member 1 (PHLDA1) was mainly distributed in type II alveolar epithelial cells in both groups but was markedly reduced in patients with emphysematous phenotype. Overexpression of PHLDA1 prevented cigarette smoke extract-stimulated apoptosis of type II alveolar epithelial cells, whereas its knockdown worsened the apoptosis. PHLDA1 binding ability to tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein epsilon (YWHAE) was weakened after exposure to cigarette smoke extract, with decreased PHLDA1 level lowering the abundance of YWHAE and attenuating the binding ability of YWHAE to p-Bad. These results demonstrate that considerable apoptosis of type II alveolar epithelial cells occurs in patients with emphysematous phenotype, and PHLDA1 may act as an effective antiapoptotic factor via YWHAE. Moreover, PHLDA1 may serve as a potential interfering target, providing insights into therapeutic strategies for emphysematous phenotype.